ANALYSIS OF FACTORS INFLUENCING ADHERENCE TO ANTIRETROVIRAL MEDICATION (ARV) IN HIV/AIDS PATIENTS BASED ON INFORMATION, MOTIVATION, BEHAVIORAL SKILLS AT CUT MEUTIA GENERAL HOSPITAL - Yuziani; Mulyati Sri Rahayu; Harvina Sawitri; Wizar Putri Mellaratna; Anna Millizia; Yofinda Aurelia Rizkita; Rani Mulya Safitri (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2023)
HIV (Human Immunodeficiency Virus), included in the Retroviridae family, is a virus that causes AIDS (Acquired Immunodeficiency Syndrome), a syndrome caused by a decrease in the body's immune system. Compliance with taking medication on HIV/AIDS clients is very important, non-adherence in implementing therapy will reduce the effectiveness of ARV drugs and even increase viral resistance in the body. Information, motivation and ability to behave are fundamental determinants of a behavior in adherence to taking medication. This study will analyze the factors associated with adherence to taking ARV medication in HIV/AIDS patients to find out the causes of nonadherence to taking ARV medication. This type of research uses descriptive research methods while based on the time dimension the research uses a cross sectional design. The research was conducted at Cut Meutia General Hospital. This research was conducted from 2018-2019. The sampling technique in this study used the total sampling method. The population in this study were all HIV/AIDS patients who were treated at the VCT and CST clinics at Cut Meutia Hospital, North Aceh District, which were recorded until 2018-2019, totaling 62 people. The results of this study found that respondents at Cut Meutia Hospital had low information of 90.0% regarding adherence to ARV drug use. Respondents at Cut Meutia Hospital had low motivation of 96.7% for adherence to ARV drug use. Respondents at Cut Meutia Hospital had low behavioral skills of 96.7% for compliance with the use of ARV drugs. The sampling technique in this study used the total sampling method. The population in this study were all HIV/AIDS patients who were treated at the VCT and CST clinics at Cut Meutia Hospital, North Aceh District, which were recorded until 2018-2019, totaling 62 people. The results of this study found that respondents at Cut Meutia Hospital had low information of 90.0% regarding adherence to ARV drug use. Respondents at Cut Meutia Hospital had low motivation of 96.7% for adherence to ARV drug use. Respondents at Cut Meutia Hospital had low behavioral skills of 96.7% for compliance with the use of ARV drugs. The sampling technique in this study used the total sampling method. The population in this study were all HIV/AIDS patients who were treated at the VCT and CST clinics at Cut Meutia Hospital, North Aceh District, which were recorded until 2018-2019, totaling 62 people. The results of this study found that respondents at Cut Meutia Hospital had low information of 90.0% regarding adherence to ARV drug use. Respondents at Cut Meutia Hospital had low motivation of 96.7% for adherence to ARV drug use. Respondents at Cut Meutia Hospital had low behavioral skills of 96.7% for compliance with the use of ARV drugs. The population in this study were all HIV/AIDS patients who were treated at the VCT and CST clinics at Cut Meutia Hospital, North Aceh District, which were recorded until 2018-2019, totaling 62 people. The results of this study found that respondents at Cut Meutia Hospital had low information of 90.0% regarding adherence to ARV drug use. Respondents at Cut Meutia Hospital had low motivation of 96.7% for adherence to ARV drug use. Respondents at Cut Meutia Hospital had low behavioral skills of 96.7% for compliance with the use of ARV drugs. The population in this study were all HIV/AIDS patients who were treated at the VCT and CST clinics at Cut Meutia Hospital, North Aceh District, which were recorded until 2018-2019, totaling 62 people. The results of this study found that respondents at Cut Meutia Hospital had low information of 90.0% regarding adherence to ARV drug use. Respondents at Cut Meutia Hospital had low motivation of 96.7% for adherence to ARV drug use. Respondents at Cut Meutia Hospital had low behavioral skills of 96.7% for compliance with the use of ARV drugs. Respondents at Cut Meutia Hospital had low motivation of 96.7% for adherence to ARV drug use. Respondents at Cut Meutia Hospital had low behavioral skills of 96.7% for compliance with the use of ARV drugs. Respondents at Cut Meutia Hospital had low motivation of 96.7% for adherence to ARV drug use. Respondents at Cut Meutia Hospital had low behavioral skills of 96.7% for compliance with the use of ARV drugs. .